Ash, Protein And Salinity Analysis Of Integrated Formulation Of Herbs And Spices In Typical Simalungun “Tinuktuk” North Sumatera-Indonesia - Damanik, Marini; Rosmiati, Risti; Permatasari, Tyas; Aulia Surbakti, Tia; Ayuni, Syarifah (CV. Inara, 2023)
Tinuknuk is a special sauce from Simalungun Regency, North Sumatra Province, tinuktuk warms the body and is believed to be able to cure various internal diseases, especially to help post-natal recovery. This study aims to determine the optimal nutritional value of the main components, namely red ginger with black pepper in the ratio composition: 70:30%, 60:40%, 50:50%, 40:60%, and 30:70% using the method oven at a temperature of 105℃. Then the ash content, protein content, and salt content were tested. The results showed that the ash content was 6.98%, respectively; 6.91%; 6.90%; 6.84%, and 6.73%. The salt content is 0.57%, respectively; 0.57%; 0.57%; 0.57%, and 0.57%. The protein content was 10.43%, respectively; 10.93%; 12.43%; 11.81%, and 10.62%.